Desenvolvimento de processos de recuperação de plasmídeos - Matos, Tiago Manuel Batista (2014)
Gene therapy is a revolutionary technique that consists in direct manipulation of the individual genetic material. DNA vaccines are based on the insertion of bacterial plasmids that are designed to express a gene into a host cell. Plasmid DNA has been used for a long time in molecular biology as a convenient mean for genetically modified living organisms. Typically amounts of DNA are needed in such operations and the methodology developed for producing and purifying the plasmid DNA has been developed accordingly. This is especially important in the safer, but less efficient non-viral gene therapy, where large amounts of plasmid DNA are required. Plasmid DNA intended for use in humans should essentially be free of genomic DNA, RNA, endotoxins, and proteins from the host cell, but also from adventitious agents such as bacteria and fungi. In addition, the plasmid vector should preferably be in the supercoiled topoisomeric form, which is a more effective transfection agent than the open-circular, linear, multimeric, or partially denatured isoforms. One very important step in any plasmid production process, after fermentation/cell harvest, is cell lysis. During this step the bacteria are broken up and intracellular components are released. Lysis is, therefore, crucial to the production as it determines both the amount of bacterial plasmid DNA actually entering the downstream process and the difficulty of the subsequent purification via the complexity of the feed matrix, i.e., the amount and type of co-released impurities. The selection of the cell lysis process, among the many that exist, depends on the purpose and type of microorganism to which it will be applied. The cell lysis processes, particularly the chemical and enzymatic, have been developed to minimize possible adverse effects that could occur to pDNA. In this work 5 different types of reported methods (Alkaline Lysis, Osmotic shock Lysis, Non Enzymatic Thermal Shock, Electrical Cell Lysis and non Alkaline) as well as a newly developed process of plasmid recovery were studied and compared in terms of their profitability.